2019
DOI: 10.1177/0972262918821248
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on Perceived Value and Attitude of Millennials Towards Social Media Advertising: A Structural Equation Modelling Approach

Abstract: The purpose of the article is to provide a comprehensive advertising model, which examines the impact of the identified predictors such as entertainment, informativeness, irritation, credibility, incentives and personalization on social media advertising value (SMAV) and further see the impact of SMAV on the attitudes of millennials towards social media advertising (ATSMA). A quantitative and deductive approach of research was followed, where data were collected using a self-administered questionnaire from 478… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
70
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 84 publications
(118 reference statements)
14
70
2
3
Order By: Relevance
“…Notably, attitude toward social media advertising received the most scholarly attention among these topics. However, a lack of theoretical foundation for hypothesis testing is apparent in the literature (Knoll, 2016), and this missing link has not been addressed in more recent years (Arora and Agarwal, 2019). Accordingly, Knoll agreed that this area of scholarly inquiry would continue to grow in the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, attitude toward social media advertising received the most scholarly attention among these topics. However, a lack of theoretical foundation for hypothesis testing is apparent in the literature (Knoll, 2016), and this missing link has not been addressed in more recent years (Arora and Agarwal, 2019). Accordingly, Knoll agreed that this area of scholarly inquiry would continue to grow in the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the consumers' perception of informativeness, entertainment, credibility and the absence of irritation were crucial and related to their attitudes towards advertisements. Even Arora and Agarwal (2019) concluded that personalisation was not a significant predictor of the social media advertising value. However, the researchers found that credibility is a determinant in affecting the advertising value.…”
Section: Personalisationmentioning
confidence: 99%
“…Individual characteristics describe individuals' lasting and stable tendencies, such as demographics and personality traits. Six variables are identified from our article set: age (Arora and Agarwal, 2019;Belanche et al, 2019;Taylor et al, 2011;Van Der Goot et al, 2016;Youn and Kim, 2019a), gender (Belanche et al, 2019;Huhmann and Limbu, 2016;Taylor et al, 2011;Tsimonis et al, 2020), culture (Abu-Ghosh et al, 2018;Deraz, 2018;Deraz and Awuah, 2015;Mansour, 2015;Muralidharan et al, 2015;Van Der Goot et al, 2016), trait reactance, regulatory and disposition to value privacy (see Table 6).…”
Section: Moderators: Individual Difference Factorsmentioning
confidence: 99%
“…Efficiency (Belanche et al, 2020;Kongsagoonwong and Ngamkroeckjoti, 2018); Attitude (Aydin, 2016(Aydin, , 2018Lin and Kim, 2016;Muralidharan et al, 2015); Value (Deraz et al, 2015a, b and c;Firat, 2019;Logan et al, 2012;Saxena and Khanna, 2013); Cognitive avoidance (Belanche et al, 2020;Guardia, 2015); Ad skepticism (Loureiro, 2018) Loyalty (Arli, 2017) Attitude (Ahn et al, 2017;Arora and Agarwal, 2019;Gaber et al, 2019;Huang, 2019;Mattke et al, 2019;Ozcelik and Varnali, 2018) Satisfaction (Alsamydai and Khasawneh, 2013); Social media fatigue (Bright and Logan, 2018) Emotional response Appeal, engagement, empowerment (Morris et al, 2016); Affective involvement (Li et al, 2017); Affective avoidance (Dodoo and Wen, 2019) --…”
Section: Cognitive Responsementioning
confidence: 99%